Professional Ethics Of Guidance And Counseling Teachers In Responding To Student Discipline Problems - Nabawi Pradisty; Uli Makmun Hasibuan; Nadira Putri Wanda (EDUCATION JOURNAL OF INDONESIA, 2024)
This research uses a qualitative approach, which uses library research methods and the data that has been collected is related to the purpose of researchers to find out how to become a professional guidance teacher in overcoming problems in a student. The data collected in this study was sourced from books, literature, and records. Regarding the professional ethics of a supervisory teacher, it is closely related to the process of establishing relationships between teachers and students, efforts to smooth the process of alleviating problems that occur within students. Therefore, teachers are required to have an ethics and professional attitude instilled in themselves to respond to student discipline problems. Discipline problems still often occur within an individual, including the case with an individual student. Disciplinary problems must be eliminated so that something negative does not arise in students. Efforts to alleviate disciplinary problems are carried out within the school environment. Where teachers are required to be able to provide an understanding of what if there is no discipline in themselves. With this, the purpose of researchers in research is to know how to become a professional teacher in alleviating disciplinary problems. Keyword : Ethics, Professional, Guidance Teacher, Discipline.